PERSEPSI GURU TENTANG PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) PADA PROSES PEMBELAJARAN DI SMK NEGERI 5 PADANG - 769-779 , Nino Afrisandy (CIVED, 2015)
ABSTRACT             The population inthis study are allteachers of SMKNegeri 5Padang, amounting to 145teachers, grab samplesrandomlyby the number of61 teachers. As for theexisting problemsin the fieldthat isnot yetfulfilledallthe operationalneedsSMK5Padangonthe learning process. This research is adescriptivethat aims toreveal theteacher's perceptionofthe SchoolOperational Assistance(BOS). Datawere statistically analyzedwiththe help ofthe programMicrosoft OfficeExcel2007 andSPSSfor windowsversion17.00. Resultsofthis research generallyshowsthat theBOSprograminthe learning processcategorizedenough.The schoolsuggestedfurther improvethe provision ofinformation to allteachersboth orallyand in writing.      .Kata kunci: Persepsi Guru, Program BOS, Proses Pembelajaran